2005
DOI: 10.1097/01.ijg.0000185617.98915.36
|View full text |Cite
|
Sign up to set email alerts
|

Audit of Trabeculectomy at a Tertiary Referral Hospital in East Africa

Abstract: The results of surgery compare well with other reported series. 5FU did not demonstrate significant benefit in terms of intraocular pressure lowering beyond 2 months postoperatively. Early postoperative hypotony should be avoided. The gender difference in intraocular pressure results has not previously been reported and deserves further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 7 publications
2
30
0
Order By: Relevance
“…The mean reduction in IOP from 32.2 mm Hg (median ¼ 30.5; SD ¼ 11.4) in the preoperative period to 17.8 mm Hg (median ¼ 17.0; SD ¼ 5.8) at a year follow-up compares with report from other previous studies. 4,[17][18][19] There was no significant difference between the 5-FU and the non-5-FU groups at a year follow-up in term of their mean IOP (P ¼ 0.6). The survival curve between the two groups also failed to demonstrate any added advantage to the use of antimetabolites.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The mean reduction in IOP from 32.2 mm Hg (median ¼ 30.5; SD ¼ 11.4) in the preoperative period to 17.8 mm Hg (median ¼ 17.0; SD ¼ 5.8) at a year follow-up compares with report from other previous studies. 4,[17][18][19] There was no significant difference between the 5-FU and the non-5-FU groups at a year follow-up in term of their mean IOP (P ¼ 0.6). The survival curve between the two groups also failed to demonstrate any added advantage to the use of antimetabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Shallow anterior chamber ranked highest in the list of early post-operative complications and is similar to what had being reported in some other previous studies. 4,12,15,[20][21] There was no clinically documented case of choroidal effusion/detachment, the incidence of which is very low among blacks compared to Caucasians. This study showed no significant correlation between the use of 5-FU and the presence of postoperative shallow anterior chamber.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations